MENGAJAR MATA PELAJARAN EKONOMI DI SMA DALAM KEGIATAN PENUGASAN DOSEN KE SEKOLAH (PDS) AGUSTUS - SEPTEMBER 2018 DI KELAS X IPS 2 SMA SRIJAYA NEGARA PALEMBANG - Ikbal Barlian (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2018)
Teaching high school economic subjects in high school is an interesting activity, besides that the learning system is different between learning in high school and faculty. Students in schools are no exception for high school students so they want subject teachers who can provide full assistance, sincerity for all the difficulties experienced by students in understanding the subject matter. The teaching experience in high school in the Lecturer-to-School Assignment (PDS) activity shows that a friendly and caring approach is favored by students, besides that teachers need to know what knowledge forms to teach, whether in the form of concepts, facts, formulas / procedures, because others other forms of knowledge the procedure teaches him. In addition, teachers need to think about how to deliver material quickly, concisely, clearly and understood by all students